2004
DOI: 10.1016/j.jvs.2003.12.040
|View full text |Cite
|
Sign up to set email alerts
|

Allograft replacement for infrarenal aortic graft infection: early and late results in 179 patients

Abstract: Early and long-term results of allograft replacement are at least similar to those of other methods to manage infrarenal aortic graft infections. Rare specific complications include early or late allograft rupture and late aortic dilatation. The more frequent late iliofemoral complications may be easily managed through the groin. These complications are significantly reduced by using cryopreserved allografts rather than fresh allografts and by not using allografts obtained from the descending thoracic aorta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
180
3
19

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(213 citation statements)
references
References 42 publications
11
180
3
19
Order By: Relevance
“…Also, availability and costs limit more widespread use. Furthermore, 5 patients in the present study were treated with fresh allografts, which are known to have even higher risk for complications 26. Despite the lack of signs of degeneration in the current cohort, we call for caution and suggest using autologous femoral veins or cryopreserved allografts if possible.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Also, availability and costs limit more widespread use. Furthermore, 5 patients in the present study were treated with fresh allografts, which are known to have even higher risk for complications 26. Despite the lack of signs of degeneration in the current cohort, we call for caution and suggest using autologous femoral veins or cryopreserved allografts if possible.…”
Section: Discussionmentioning
confidence: 81%
“…Cryopreservation has improved the permanence of allografts, but degeneration, possible aneurysmatic dilatation, and subsequent rupture remain challenging 22, 26, 27, 28. Also, availability and costs limit more widespread use.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that cryopreserved allograft replacement is an effective and durable alternative for the treatment of aortic prosthetic graft infection, with improved outcomes in comparison with the traditional treatment of graft excision and extra-anatomic bypass grafting. But concerns about their availability, preservation, and risk of later deterioration avoids the widespread use of this alternative [10][11][12][13][14]. …”
Section: Discussionmentioning
confidence: 99%
“…A major drawback of cryopreserved allografts is the risk of degeneration leading to calcifi cation, dilatation, or even rupture. Kieffer (44) referred that the use of cryopreserved allograft is of particular benefi t in patients with AEF reducing the one-year mortality rate from 34 % with the use of conventional grafts to 9 %. The major problem of the use of allografts is their shortage especially in hospitals without allograft banks, as well as in hospitals not involved in transplantation program.…”
Section: Treatment Optionsmentioning
confidence: 99%